Can the gut-brain axis provide insight into psilocybin's therapeutic value in reducing stress? - Alanna Kit; Kate Conway; Savannah Makarowski; Grace O'Regan; Josh Allen; Sandy R. Shultz; Tamara S. Bodnar; Brian R. Christie (Neurobiology of Stress)
There is growing interest in exploring the therapeutic potential and mechanisms of action of psilocybin on stress-related neuropsychiatric disorders, including depression, generalized anxiety disorder (GAD), post-traumatic stress disorder (PTSD), obsessive-compulsive disorder (OCD), addiction, and disordered eating. Despite promising progressions in preclinical and clinical research, the neurobiological and physiological mechanisms underlying the therapeutic effects of psilocybin remain complex, involving multiple systems with numerous homeostatic feedback signaling pathways throughout the body. This review paper explores how psilocybin mechanistically interacts with the gut microbiota, enteric nervous system, hypothalamic-pituitary axis, and how psilocybin influences the bidirectional communication between peripheral and neuronal systems. Shifting towards a more integrated paradigm to unravel the mechanisms through which psilocybin affects the bidirectional gut-brain axis holds the promise of significantly advancing our understanding of psilocybin-based therapies from preparation of treatment, administration, to proceeding long-term integration. Such an understanding can extend beyond the treatment of psychiatric disorders, further encompassing a broader spectrum of inflammatory-related disorders.